FROM CLICKS TO CUSTOMERS: MANAGING THE FULL FUNNEL FOR SUSTAINABLE GROWTH - Sarjani; Lukmanul Hakim; Dahrul Aman Harahap (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
In the digital marketing landscape, a pervasive focus on top-funnel metrics like clicks and impressions often neglects downstream conversion and retention, leading to inefficient spend and unsustainable growth. This study addresses the critical need for an integrated, full-funnel management strategy that aligns marketing activities with long-term customer value. The objective is to demonstrate how a holistic funnel approach, from awareness to advocacy, enhances customer acquisition cost (CAC) efficiency and lifetime value (LTV). Employing a mixed-methodology approach, the research analyzed performance data from a multi-brand portfolio over 18 months and conducted in-depth interviews with marketing executives. The results indicate that organizations implementing integrated funnel management achieved a 24% improvement in CAC and a 35% increase in customer retention rates. The discussion highlights the importance of data integration, cross-channel orchestration, and aligning KPIs across funnel stages. It is concluded that sustainable growth is contingent on shifting from isolated campaign tactics to a cohesive, customer-centric funnel strategy, ensuring marketing efforts contribute directly to enduring business health.